GRIT IN MEDICAL PROFESSIONAL EDUCATION STUDENTS - Rusdi Rusli; Nur Ainy Fardana; Wiwin Hendriani (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Grit is one of the noncognitive predictors that must be owned by medical professional education students in taking professional education. Grit consists of consistency of interest and perseverance of efforts to deal with various conditions that will be encountered in pursuing the educational process. The purpose of this study was to determine how the level of grit in medical internship students in Indonesia. Methods: This research method used online survey research methods. The procedure for filling out the questionnaire is distributed online and the respondent voluntarily completes the questionnaire with the criteria of the respondent namely active professional medical education students who have completed the profession for at least one year. The survey was responded by 708 medical professional education students from 21 universities that organize medical professional education in Indonesia. Results: The results of grit categorization for medical professional education students were based on five categories: 2 respondents had very low grit levels and 52 respondents with low grit categories. Meanwhile, 238 respondents had moderate grit levels, 314 respondents were in the high category, and 102 respondents were in the very high category. In addition, there is no difference between the average grit scores of medical professional education students who have passed the study period of one, two, or three years. Conclusion: There are variations in grit levels obtained from the results of this study. Grit is a strong predictor for work performance and also academic performance. Individuals with a high degree of grit will be more diligent at work, do not easily give up if they fail, and can even make failure as motivation to strive and be more active in achieving goals. Apart from assessing the cognitive abilities of medical students, it is hoped that the assessment of non-cognitive factors in the form of grit measurement at the beginning of selection and during the medical education process can be carried out both at the pre-clinical stage and at the clinical stage. This aims to determine the level of business persistence and consistency of student interest in the medical field.